2018
DOI: 10.1002/etep.2768
|View full text |Cite
|
Sign up to set email alerts
|

A combined approach for power system stabilizer design using continuous wavelet transform and SQP algorithm

Abstract: Summary Operation and control of large‐scale power systems is a complex task. Since the primary purpose of power system stabilizer (PSS) units is damping of local and interarea modes, identification of network electromechanical oscillatory modes for designing PSS is very important. In this research, continuous wavelet transform (CWT) was used to study low‐frequency electromechanical oscillations of power systems. The complex Morlet mother wavelet and guidelines for the selection of center frequency, bandwidth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 37 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…SQP is executed in numerous optimisation models of numerous complexes as well as non-stiff systems. Presently, it is used to investigate the guidewire deformation in blood vessels [42], in the power system stabiliser design [43], optimal control of rapid cooperative rendezvous [44], 3D deformable prostate model pose estimation in minimally invasive surgery [45], deterministic constrained production optimisation of hydrocarbon reservoirs [46], prediction differential system [47] and in the optimisation of an auxetic jounce bumper [48]. To switch the sluggishness of GA, hybridisation of the GA-SQP process is implemented along with the necessary steps, as provided in Table 1.…”
Section: Optimisation Measures: Mwnns-ga-sqpmentioning
confidence: 99%
“…SQP is executed in numerous optimisation models of numerous complexes as well as non-stiff systems. Presently, it is used to investigate the guidewire deformation in blood vessels [42], in the power system stabiliser design [43], optimal control of rapid cooperative rendezvous [44], 3D deformable prostate model pose estimation in minimally invasive surgery [45], deterministic constrained production optimisation of hydrocarbon reservoirs [46], prediction differential system [47] and in the optimisation of an auxetic jounce bumper [48]. To switch the sluggishness of GA, hybridisation of the GA-SQP process is implemented along with the necessary steps, as provided in Table 1.…”
Section: Optimisation Measures: Mwnns-ga-sqpmentioning
confidence: 99%
“…These have considerable effect on its performance and may not effectively damp out the LFO in the system. Conventional PSS parameter design problem is a cumbersome exercise where many analytical methods were proposed in the literature like the eigenvalue method, gradient methods for optimization, numerical programing method, robust control method, H ∞ method and so on 9,10 . However, it was reported that, for the design of PSS for interconnected multimachine systems operating on different conditions and configurations, these numerical methods involves representing the system mathematical models which is difficult for large system.…”
Section: Introductionmentioning
confidence: 99%
“…They have a substantial impact on its performance and may fail to successfully suppress the LFO in the system. Conventional PSS parameter design is a burdensome implementation, and many mathematical methods were proposed in the literature, such as the eigenvalue method, gradient methods for optimization, numerical programming method, robust control method, H ∞ method, and so on [11,12]. However, it was shown that, for the design of PSS for large interconnected multi-machine power systems operating on different operating conditions and structures, mathematical approaches take a long time to evaluate the system's mathematical models, and the optimum PSS design is from time to time incorrect [13][14][15].…”
Section: Introductionmentioning
confidence: 99%